Consumer potential analysis of feasibility criteria of geothermal projects - Jenei, Tünde (Applied Studies in Agribusiness and Commerce, 2012)
The University of Debrecen, Faculty of Engineering, has been conducting a research program in geothermal energy since 2008. This program enabled me to devise an analytical study of the monetary and non-monetary criteria of geothermal projects. The monetary criteria of a region or a location for geothermal energy production cover the investment costs of the surface installations and the cost of the drillings. Non-monetary criteria include the geological and geothermal evaluations of a reservoir and the evaluation of consumer potential. This paper represents a small part of the larger study and focuses on consumer potential.